Perintah Menggunakan Sinyal Suara dengan Mel-Frequency Cepstral Coefficients (MFCC) dan K-Nearest Neighbor (KNN) - Aryo Widano, Gusti Putu; Karyawati, Anak Agung Istri Ngurah Eka (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
Technological developments today allow every action that originally required more energy to complete will become more practical, an input to give a command can not only be done with a mouse, keyboard, or touch screen technology but can also be done with the help of voice with the help of data by the user computer. Before it can be used as a command, first go through the voice feature extraction process using the Mel-Frequency Cepstral Coefficients (MFCC) method and the classification process using the K-Nearest Neighbor (KNN) method. Previously someone conducted a similar study, with the classification used being Learning Vector Quantization (LVQ) and the highest accuracy obtained ? 0.1.